2013
DOI: 10.1118/1.4788657
|View full text |Cite
|
Sign up to set email alerts
|

Delivery confirmation of bolus electron conformal therapy combined with intensity modulated x-ray therapy

Abstract: Bolus ECT and mixed beam therapy dose delivery to the phantom were more accurate than IMXT delivery, adding confidence to the use of planning, fabrication, and delivery for bolus ECT tools either alone or as part of mixed beam therapy. The methodology reported in this work could serve as a basis for future standardization of the commissioning of bolus ECT or mixed beam therapy. When applying this technology to patients, it is recommended that an electron dose algorithm more accurate than the pencil beam algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…For plans without VMAT component, the prescription dose was changed from 40 to 50 Gy for the BECT and supraclavicular IMRT fields to make them clinically comparable. Consistent with previous study, 17 the mixed beam reduced the hot spots within and outside the target at the expense of increased low dose outside PTV. Figures 5-7 show the dose distributions and dose volume histograms (DVHs) for patients CW2 and CW6 from mixed beam therapy.…”
Section: F Statistical Analysissupporting
confidence: 91%
See 3 more Smart Citations
“…For plans without VMAT component, the prescription dose was changed from 40 to 50 Gy for the BECT and supraclavicular IMRT fields to make them clinically comparable. Consistent with previous study, 17 the mixed beam reduced the hot spots within and outside the target at the expense of increased low dose outside PTV. Figures 5-7 show the dose distributions and dose volume histograms (DVHs) for patients CW2 and CW6 from mixed beam therapy.…”
Section: F Statistical Analysissupporting
confidence: 91%
“…Smoothing the machineable wax bolus reduced some of the dose heterogeneities, but not all could be removed because of bolus surface following the curvature of chest wall. Mixing VMAT with BECT + IMRT (1:4) reduced, but did not eliminate dose heterogeneities, as was the case reported previously …”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…26 With the recent commercial availability of bolus ECT, knowing the accuracy of the PBA and PBRA dose calculations in the presence of bolus is of clinical interest. A recent study of the accuracy of the dose delivery of bolus ECT and mixed beam therapy (intensity-modulated x-ray therapy optimized on top of bolus ECT dose distributions) to chest wall and parotid PTVs embedded in a homogeneous cylindrical phantom by Kavanaugh et al 27 showed for the bolus ECT dose component that the PBA calculations agreed with measured data to within 4% or 2 mm for 98.8% and 97.3% of points for parotid and chest wall plans, respectively. Kavanaugh 28 showed similar accuracy for the PBRA, i.e., dose calculations agreed with measured data to within 4% or 2 mm for 98.9% and 98.7% of points for the same parotid and chest wall plans, respectively.…”
Section: Introductionmentioning
confidence: 99%